Overview of Methods for Overcoming Hindrance to Drug Delivery to Tumors, with Special Attention to Tumor Interstitial Fluid - Baronzio, Gianfranco; Parmar, Gurdev; Baronzio, Miriam (Frontiers in Oncology, 2015)
Every drug used to treat cancer (chemotherapeutics, immunologic, monoclonal antibodies, nanoparticles, radionuclides) must reach the targeted cells through the tumor environment at adequate concentrations, in order to exert their cell-killing effects. For any of these agents to reach the goal cells they must overcome a number of impediments created by the tumor microenvironment, beginning with tumor interstitial fluid pressure (TIFP) and a multifactorial increase in composition of the extracellular matrix (ECM). A primary modifier of tumor microenvironment is hypoxia, which increases the production of growth factors such as vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF). These growth factors released by both tumor cells and bone marrow recruited myeloid cells (MDS), form abnormal vasculature characterized by vessels that are tortuous and more permeable. Increased leakiness combined with increased inflammatory byproducts accumulates fluid within the tumor mass [tumor interstitial fluid (TIF)], ultimately creating an increased pressure (TIFP). Fibroblasts are also up-regulated by the tumor microenvironment, and deposit fibers that further augment the density of the extracellular matrix (ECM), thus, further worsening the TIFP. Increased TIFP with the ECM are the major obstacles to adequate drug delivery. By decreasing TIFP and decreasing ECM density, we can expect an associated rise in drug concentration within the tumor itself. In this overview we will describe all the methods (drugs, nutraceuticals, physical methods of treatment) able to lower TIFP and to modify ECM that can be used for increasing drug concentration within the tumor tissue.